Paradigm shift in education and upbringing: the influence of modern educational philosophy - Kovalchuk, Volodymyr; Dolinska, Ludmila; Marushchak, Yaroslav (Technium Education and Humanities, 2024)
The article is devoted to the study of the formation of methodological foundations of one of the priority branches of humanitarian knowledge - philosophy of education. The author proposes a concept of methodological foundations of the philosophy of education, which is aimed at overcoming the problems of modern educational activity and development of humanitarian knowledge in general, since the concept of ‘human education’ is a field of intersection of different branches of knowledge. The essence of the concept is to formulate the structural elements of the philosophy of education on the basis of identifying and analyzing existing contradictions and paradoxes in modern educational activities.